Two distinct subtypes of obsessive compulsive disorder revealed by heterogeneity through discriminative analysis. Issue 10 (5th April 2022) - Han, Shaoqiang; Xu, Yinhuan; Guo, Hui‐Rong; Fang, Keke; Wei, Yarui; Liu, Liang; Cheng, Junying; Zhang, Yong; Cheng, Jingliang
Abstract: Neurobiological heterogeneity in obsessive compulsive disorder (OCD) is understudied leading to conflicting neuroimaging findings. Therefore, we investigated objective neuroanatomical subtypes of OCD by adopting a newly proposed method based on gray matter volumes (GMVs). GMVs were derived from T1‐weighted anatomical images of patients with OCD ( n = 100) and matched healthy controls (HCs; n = 106). We first inquired whether patients with OCD presented higher interindividual variability HCs in terms of GMVs. Then, we identified distinct subtypes of OCD by adopting heterogeneity through discriminative analysis (HYDRA), where regional GMVs were treated as features. Patients with OCD presented higher interindividual variability than HCs, suggesting a high structural heterogeneity of OCD. HYDRA identified two distinct robust subtypes of OCD presenting opposite neuroanatomical aberrances compared with HCs, while sharing indistinguishable clinical and demographic features. Specifically, Subtype 1 exhibited widespread increased GMVs in cortical and subcortical regions, including the orbitofrontal gyrus, right anterior insula, bilateral hippocampus, and bilateral parahippocampus and cerebellum. Subtype 2 demonstrated overall decreased GMVs in regions such as the orbitofrontal gyrus, right anterior insula, and precuneus. When mixed together, none of patients presented significant differences compared with HCs. In addition, the total intracranial volume of Subtype 2 was significantly correlated with the total score of the Yale–Brown Obsessive Compulsive Scale while that of Subtype 1 was not. These results identified two distinct neuroanatomical subtypes, providing a possible explanation for conflicting neuroimaging findings, and proposed a potential objective taxonomy contributing to precise clinical diagnosis and treatment in OCD. Abstract : We observed high heterogeneity in terms of gray matter volume across patients with OCD and revealed two robust neuroanatomical subtypes of OCD. These two subtypes exhibited remarkably opposite gray matter volume aberrances compared to healthy controls. Our results provide a possible explanation for the conflicting neuroimaging findings and an objective taxonomy contributing to precision clinical diagnosis and treatment of OCD.